Nature Speaks: Agency and Environment in Ben Okri’s The Famished Road - Ogungbemi, Olarotimi (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
This study explores the linguistic strategies in Ben Okri’s “The Famished Road” to construct ecological interdependencies and agency in the novel. Employing systemic functional linguistics and ecolinguistic analysis, the study examines how Okri’s linguistic strategies elevate the agency of non-human elements, representing them as vibrant and willful participants within their ecosystem. The purpose of this analysis is to understand how language in “The Famished Road” conveys agency and a symbiotic relationship between humans and non-human elements, thereby addressing broader ecological and environmental concerns. Employing an ecolinguistic analysis, the research examines linguistic portrayals that challenge anthropocentric views and emphasize respect for nature. Results show that the novel frames nature and non-human entities as vibrant, active participants, influencing ecological consciousness and fostering ethical considerations towards the environment. This study concludes that Ben Okri’s ‘The Famished Road’, through its unique linguistic strategies, reflects and advocates for a symbiotic relationship between all life forms, highlighting the potential of literary works to contribute to environmental advocacy and consciousness. This analysis adds depth to our understanding of language’s role in ecological literature and encourages further exploration into how textual practices can influence ecological and ethical perceptions.